Gender Perspective of Planners as a Gender Focal Point in the Provincial Government of Central Sulawesi - Irmawati Sahi; Muhammad Khairil; Ritha Safitri (Khazanah Sosial, 2024)
This study examines the gender perspective of planners in regional apparatus organizations (OPD) within the Central Sulawesi Provincial Government, focusing on their roles as gender focal points in development planning. Using Peter Berger and Thomas Luckmann’s (1966) Social Construction Theory—comprising externalization, objectification, and internalization—this qualitative research, conducted from September 2024 to February 2025, employs purposive sampling to select informants from key OPDs involved in gender-based planning, including the Regional Development Planning Agency, the Inspectorate, the Women’s Empowerment and Child Protection Office, the Education Office, the Population Control and Family Planning Office, and the Central Sulawesi Social Service. Primary data will be collected through in-depth interviews and direct observations of gender mainstreaming (PUG) activities, while secondary data will be sourced from government policies, academic articles, official websites, and books. Data analysis follows the interactive model of Miles, Huberman, and Saldana (2014), which includes data collection, data condensation, data display, and conclusion drawing. The findings reveal that OPD planners generally exhibit biases in their approach to gender mainstreaming (PUG), where the externalization stage shows varied understandings of PUG alongside efforts to promote gender-responsive development planning, the objectification stage reflects critical perspectives on gender-responsive policies in infrastructure, education, and health, and the internalization stage highlights challenges in fully integrating gender considerations into regional development planning. This study emphasizes the need for capacity-building programs to strengthen planners’ gender perspectives and recommends greater institutional support for sustainable gender mainstreaming in regional governance.